Pendampingan Dosen dan Mahasiswa STIBANKS Semester Akhir dalam Sitasi Menggunakan Mendeley - Supriatna, Encep (Ma'soem University, 2021)
Creating a table of contents, table of tables, list of figures, and bibliography manually will be a hassle for writers, especially when editing of content occurs which has an impact on shifting page numbers, or changes in page format or reference style. This community service is carried out using the service learning method, to add insight to lecturers and final semester students at the Al Ma'soem Islamic Banking College. By providing insight into the technique of creating documents in Microsoft Word so that it can present a table of contents, table list, list of images automatically, Mendeley installation, how to add references to Mendeley, how to cite with Mendeley, automatically present a bibliography, and change the style as needed. With this training, it is hoped that it can add insight to lecturers and students in writing articles or research results correctly and easily in accordance with applicable rules/rules.